CO2 utilization: Turning greenhouse gas into fuels and valuable products. (15th April 2020) - Anwar, M.N.; Fayyaz, A.; Sohail, N.F.; Khokhar, M.F.; Baqar, M.; Yasar, A.; Rasool, K.; Nazir, A.; Raja, M.U.F.; Rehan, M.; Aghbashlo, M.; Tabatabaei, M.; et al.
Abstract: This study critically reviews the recent developments and future opportunities pertinent to the conversion of CO2 as a potent greenhouse gas (GHG) to fuels and valuable products. CO2 emissions have reached an alarming level of around 410 ppm and have become the primary driver of global warming and climate change leading to devastating events such as droughts, hurricanes, torrential rains, floods, tornados and wildfires across the world. These events are responsible for thousands of deaths and have adversely affected the economic development of many countries, loss of billions of dollars, across the globe. One of the promising choices to tackle this issue is carbon sequestration by pre- and post-combustion processes and oxyfuel combustion. The captured CO2 can be converted into fuels and valuable products, including methanol, dimethyl ether (DME), and methane (CH4 ). The efficient use of the sequestered CO2 for the desalinization might be critical in overcoming water scarcity and energy issues in developing countries. Using the sequestered CO2 to produce algae in combination with wastewater, and producing biofuels is among the promising strategies. Many methods, like direct combustion, fermentation, transesterification, pyrolysis, anaerobic digestion (AD), and gasification, can be used for the conversion of algae into biofuel. Direct air capturing (DAC) is another productive technique for absorbing CO2 from the atmosphere and converting it into various useful energy resources like CH4 . These methods can effectively tackle the issues of climate change, water security, and energy crises. However, future research is required to make these conversion methods cost-effective and commercially applicable. Graphical abstract: Image 104 Highlights: Recent advancements in carbon capture and utilization (CCU) was examined. CCU is promising to mitigate global warming and climate change. CCU is effectively in practice and captured CO2 is used for value-added products. Various analyses validate CCU as economically viable and environment-friendly. Biofuel and chemical production along desalination should be integrated with CCU.